Observations of playground play during elementary school recess - Massey, William V. (BMC Res Notes, 2018)
OBJECTIVE: The purpose of the current study was to examine reliability and validity evidence for an observational measure of playground play during recess. Observational data of what children played at recess were collected at 236 recess sessions across 26 urban elementary schools. An inductive content analysis of children’s type of play and activity engagement during recess was conducted to categorize activities. Inter-rater reliability of observations was assessed at 49 points that spanned 22 unique recess periods at four different schools. Reliability data were collected during the winter and spring seasons. A multivariate analysis of variance was conducted to examine differences in play and activity patterns between genders, and between schools implementing recess interventions (e.g., structured play environment) and schools with no recess intervention. RESULTS: Results of the content analysis yielded eight playground play and activity categories, all with high levels of inter-rater reliability (ICCs > .90). Significant differences in children’s play and activity patterns emerged between genders and across recess intervention conditions. Engagement in ‘sports and organized activities’ and ‘non-engagement in play’ contributed most to the separation between boys and girls, while ‘non-engagement in play’ contributed most to the separation between recess intervention and non-intervention schools.